PENGARUH PENGGUNAAN ASI DAN REBUSAN DAUN KERSEN TERHADAP LAMA WAKTU PERAWATAN PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS DI KLINIK CITRA KECAMATAN PATUMBAK KABUPATEN DELI SERDANG - Andayani Boang Manalu; Tetty Junita Purba (Jurnal Doppler, 2021)
The birth process occurs naturally when the time has come. However, this process can lead to problems such as trauma to the delivery mother, namely trauma to the perineal area. Perineal trauma is usually a tear, can occur spontaneously or intentionally with an episiotomy. Tear if not handled properly and immediately it can cause postpartum infection problems because the wound becomes a place for germs to grow. The purpose of this study was to analyze the effect of using breast milk and decoction of kersen leaves stew on the length of time for perineal wound care at Citra Marendal Clinic. The method used in this study was Posttest Only Control Group Design. The postpartum mother took a sample of 62 respondents with inclusion criteria and used two groups based on breast milk treatment 31 respondents and 31 respondents with decoction of cherry leaves. Statistical test analysis using the Mann Whitney test, the P-value is (0.032) < (0.05) with a z-count value of 2.139, then H0 is rejected and Ha is accepted, meaning that the perineal wound healing process in the intervention group that was given breast milk was faster than the group. intervention given the decoction of kersen leaves stew.